2013
DOI: 10.1016/j.jcf.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled aztreonam lysine vs. inhaled tobramycin in cystic fibrosis: A comparative efficacy trial

Abstract: AZLI demonstrated statistical superiority in lung function and a reduction in acute pulmonary exacerbations compared to TNS over 3 treatment courses (ClinicalTrials.gov: NCT00757237).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 15 publications
(15 reference statements)
8
101
1
7
Order By: Relevance
“…To evaluate whether the magnitude of the model-predicted improvement in FEV 1 % predicted due to LAI was consistent with the magnitude of effect observed for patients with CF receiving other antibacterial agents, the results of four clinical studies in which patients with CF received treatment with either 112 mg of tobramycin inhalation powder twice daily or 75 mg of inhaled aztreonam lysine thrice daily were assessed (14)(15)(16)(17). Given that the baseline characteristics for the average patient who received treatment with LAI (i.e., 22 years of age with a BMI of 20 kg/m 2 and a baseline FEV 1 % predicted of 66%) were similar to those described in the other four studies (i.e., patients who were 25 to 29 years of age with a BMI of 20 to 21 kg/m 2 and a baseline FEV 1 % predicted of 52% to 55%), such comparisons for improvement in the FEV 1 % predicted among agents were considered appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate whether the magnitude of the model-predicted improvement in FEV 1 % predicted due to LAI was consistent with the magnitude of effect observed for patients with CF receiving other antibacterial agents, the results of four clinical studies in which patients with CF received treatment with either 112 mg of tobramycin inhalation powder twice daily or 75 mg of inhaled aztreonam lysine thrice daily were assessed (14)(15)(16)(17). Given that the baseline characteristics for the average patient who received treatment with LAI (i.e., 22 years of age with a BMI of 20 kg/m 2 and a baseline FEV 1 % predicted of 66%) were similar to those described in the other four studies (i.e., patients who were 25 to 29 years of age with a BMI of 20 to 21 kg/m 2 and a baseline FEV 1 % predicted of 52% to 55%), such comparisons for improvement in the FEV 1 % predicted among agents were considered appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The response to aerosolized tobramycin, as assessed by change in spirometry, becomes attenuated after extended exposure, a phenomenon that is not explained by selection of bacterial populations with decreased in vitro tobramycin susceptibilities 7,8 . It is likely that a similar attenuation of efficacy will occur for other inhaled antimicrobials with extended exposure 9 . In addition some patients are unable to tolerate particular inhaled antibiotic formulations 10,11 while others may find an inhaled therapy an excessive treatment burden resulting in poor adherence 12 .…”
Section: Introductionmentioning
confidence: 94%
“…Noninferiority studies have shown that it is comparable, if not superior, to TIS in nontreatment-naive individuals with respect to increases in lung function (69). When used in trials for patients with CF with chronic B. cepacia complex infection, however, inhaled aztreonam did not result in any statistically significant improvement in FEV 1 or decreases in sputum bacterial density compared with placebo (70).…”
Section: Ats Seminarsmentioning
confidence: 99%